Polyfluorenes - Scherf, Ullrich; Neher, Dieter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
see table of contents.
Bridged Polyphenylenes – from Polyfluorenes to Ladder Polymers -- Polyfluorenes for Device Applications -- Poly(dibenzosilole)s -- Poly(2,7-carbazole)s and Related Polymers -- Polyfluorenes with On-Chain Metal Centers -- Fluorene-Based Conjugated Oligomers for Organic Photonics and Electronics -- Polyfluorene Photophysics -- Structure and Morphology of Polyfluorenes in Solutions and the Solid State -- Optically Active Chemical Defects in Polyfluorene-Type Polymers and Devices -- Single Molecule Spectroscopy of Polyfluorenes.
Keywords: Polymers .; Amorphous substances; Complex fluids; Physical chemistry; Organic chemistry; Polymer Sciences; Soft and Granular Matter, Complex Fluids and Microfluidics; Physical Chemistry; Organic Chemistry